75 Towards improving holistic care of our patients: facilitating appropriate recognition and management of co-occurring mental health problems in paediatric populations. (4th October 2017) - Bryant-Waugh, R; DeJong, M; Mora, M; Shepherd, D
Abstract : Background: As NHS service providers, there is an expectation that we shape working practices in line with the vision outlined in the Five Year Forward View Implementation Plan. This includes as requirement: 'measurable progress towards the parity of esteem for mental health enshrined in the NHS Constitution, particularly for those in vulnerable situations'. Our GOSH patient population, comprising children and young people with some of the rarest and most difficult to treat medical conditions, falls into this category. Project: As part of our legal and constitutional responsibility, we have developed, piloted and begun to implement a pathway protocol for screening patients with long term physical health conditions for mental health problems. The protocol includes appropriate follow-through of those identified as most likely to be affected. Participation in a CQUIN (Commissioning for Quality and Innovation) initiative provided the impetus, and the implementation of the pathway currently forms the focus of an audit project. This presentation covers the detail of the screening and follow- through protocol, highlighting the need for collaboration between multiple staffing groups (including staff from clinical, divisional management, Quality Improvement, and Information Services teams). The pathway is innovative and, to our knowledge, the first of its kind to be evaluated in a paediatric hospital setting. It includes the use of an iPad administered, robust, mental health screening tool (Strengths and Difficulties Questionnaire); a standardised assessment interview for those scoring above threshold, linked with electronic completion of the Current View Tool; and subsequent signposting to the most likely source of appropriate help, based on the THRIVE model. Preliminary results will be presented, to include: rates of patients screened across four long term condition specialities (nephrology, metabolic medicine, gastroenterology, and neurology). percentage identified as likely to be affected by co-occurring mental health problems. the nature and severity of these. the action taken once identified.